2018
DOI: 10.1097/ftd.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

An Improved LC-ESI-MS/MS Method to Quantify Pregabalin in Human Plasma and Dry Plasma Spot for Therapeutic Monitoring and Pharmacokinetic Applications

Abstract: Proposed method involves simple and rapid steps of sample processing that do not require a precolumn or postcolumn derivatization procedure. The method is suitable for routine pharmacokinetic analysis and therapeutic monitoring of PGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The described assays were proved to be appropriate also for the analysis of PGB in serum and blood [146][147][148]. Moreover, the validated methods for determination of the drug in plasma were reported, including LC-FLD method after derivatization with 4-fluoro-7-nitrobenzofurazan [150] and highly sensitive LC-MS/MS method [151].…”
Section: Gabapentin Pregabalin and Tiagabinementioning
confidence: 97%
See 2 more Smart Citations
“…The described assays were proved to be appropriate also for the analysis of PGB in serum and blood [146][147][148]. Moreover, the validated methods for determination of the drug in plasma were reported, including LC-FLD method after derivatization with 4-fluoro-7-nitrobenzofurazan [150] and highly sensitive LC-MS/MS method [151].…”
Section: Gabapentin Pregabalin and Tiagabinementioning
confidence: 97%
“…Isolation of both drugs from biological matrix before chromatographic analysis was performed using protein precipitation with acetonitrile [78,147] and methanol [146], or SPE using cation exchange cartridges [151]. The LC-MS/MS methods were also reported for determination of PGB in DBS/DPS [151,152]. The drug was isolated from the matrix using LLE with a mixture of methyl tert-butyl ether and diethyl ether [151] or ethyl acetate [152].…”
Section: Gabapentin Pregabalin and Tiagabinementioning
confidence: 99%
See 1 more Smart Citation
“…Information about internal standards, analytical methods and ranges, sampling methods, punch sizes, paper types, sample and injection volumes, drying times, DBS sample extraction methods, effects of Hct levels and results of comparisons between DBS and plasma were summarized (Table ). In 26 studies, 19 types of AEDs were measured using the DBS method ; among them, 9 studies analysed >2 AEDs . The most frequently analysed AED was carbamazepine (n = 8); others included lamotrigine (n = 7), valproic acid (n = 7), levetiracetam (n = 3), phenytoin (n = 3), topiramate (n = 3), carbamazepine epoxide (n = 2), gabapentin (n = 2), phenobarbital (n = 2), pregabalin (n = 2), clobazam (n = 1), clonazepam (n = 1), ethosuximide (n = 1), felbamate (n = 1), monohydroxycarbamazepine (n = 1), nitrazepam (n = 1), rufinamide (n = 1), vigabatrin (n = 1) and zonisamide (n = 1).…”
Section: Aed Concentration Measurement Using Dbs or Dpsmentioning
confidence: 99%
“…Only one bioequivalence study in healthy volunteers compared the C dps and C p of pregabalin and found that C dps could be converted to C p without introducing any statistical bias . Another study compared C dps and C dbs after adjustment for Hct levels and found a high correlation ( r 2 = 0.977) .…”
Section: Aed Concentration Measurement Using Dbs or Dpsmentioning
confidence: 99%